Natural clay-supported palladium catalysts for methane oxidation reaction: effect of alloying - Yahia H. Ahmad (18623995) (2019)
The catalytic combustion of methane (CCM) has been extensively studied owing to the wide use of methane in motor vehicles and power generation turbines. However, the absence of polarizability and the high C–H bond strength are considered to be the main drawbacks that limit its oxidation by traditional catalytic converters. Palladium-based catalysts are recognized as the benchmark catalysts for methane oxidation, especially under oxidizing conditions, and their activity is dependent on different parameters such as size, dispersion, and the nature of the support. Additionally, metal oxides are the most common supports used for CCM; however, they can become saturated with water, especially during steady-state operation at low temperatures, owing to their hydrophilic nature. This causes saturation of the active sites with OH species, which poisons the active centers of the catalyst, prevents activation of methane molecules, and induces catalyst sintering. Herein, we reported the synthesis of a binary palladium nanoalloy on a halloysite nanotube support (PdM@Hal). This one-pot synthesis procedure was performed via ultrasound-enhanced reduction of metal precursors in aqueous solution containing dispersed halloysite nanotubes, using NaBH4 as reducing agent. Transmission electron microscopy revealed that the synthesized PdM@Hal catalysts preserved the morphology of the pristine support after synthesis and calcination, with good dispersion of the catalyst on the surface of the support. Promoted metal-support interactions revealed enhanced catalytic performance, following the order PdNi > PdCo > Pd > PdCu, with activation energies of 68–94 kJ mol−1. Other Information Published in: RSC Advances License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://doi.org/10.1039/c9ra06804j